Rumusan Kebijakan Penataan Reklame di Kota Semarang - Rina Kurniati; Muhammad Fajri Nugraha (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
The rapid growth of billboards that are used as a medium of communication and marketing of products and services, one of which is caused by increasing community needs and development of technology & information. The rapid growth must be responded to well by the Semarang City Government so that strategic points for regional income can be maximized while maximizing spatial planning efforts in Semarang City. Based on this, the research itself aims to formulate a billboard structuring policy in the city of Semarang by using a qualitative descriptive method. The formulation efforts were carried out through several analysis points which resulted in each building function and land use affecting the provisions relating to billboards and the development of advertisement plots on private land to be controlled because they were related to environmental aesthetics, road benefits and road space could also be used for advertising and information media provided that they get permission from the road organizer according to their authority.